Diary of a wimpy kid : dog days - Kinney, Jeff. (New York : Amulet Books, 2009)
Greg Heffley recounts his daily experiences during summer vacation as he tries to live out his ultimate fantasy of spending the days indoors playing video games with no responsibilities and no rules, despite his mother's attempts to pack the summer with outdoor activities and family fun.
Pub Weekly, October 2009
Booklist, October 2009
Horn Book, October 2010
5.4
5-8
5-8
Keywords: Summer -- Juvenile fiction; Diaries -- Juvenile fiction; Summer -- Fiction; Diaries -- Fiction; Humorous stories; Summer -- Fiction; Diaries -- Fiction; Humorous fiction; Humorous fiction